Automated registration of tail bleeding in rats - Johansen, Peter B.; Henriksen, Lars; Andresen, Per R.; Lauritzen, Brian; Jensen, Kåre L.; Juhl, Trine N.; Tranholm, Mikael (Thrombosis and Haemostasis, 2008)
An automated system for registration of tail bleeding in rats using a camera and a user-designed PC-based software program has been developed. The live and processed images are displayed on the screen and are exported together with a text file for later statistical processing of the data allowing calculation of e.g. number of bleeding episodes, bleeding times and bleeding areas. Proof-of-principle was achieved when the camera captured the blood stream after infusion of rat whole blood into saline. Suitability was assessed by recording of bleeding profiles in heparintreated rats, demonstrating that the system was able to capture on/off bleedings and that the data transfer and analysis were conducted successfully. Then, bleeding profiles were visually recorded by two independent observers simultaneously with the automated recordings after tail transection in untreated rats. Linear relationships were found in the number of bleedings, demonstrating, however, a statistically significant difference in the recording of bleeding episodes between observers. Also, the bleeding time was longer for visual compared to automated recording. No correlation was found between blood loss and bleeding time in untreated rats, but in heparinized rats a correlation was suggested. Finally, the blood loss correlated with the automated recording of bleeding area. In conclusion, the automated system has proven suitable for replacing visual recordings of tail bleedings in rats. Inter-observer differences can be eliminated, monotonous repetitive work avoided, and a higher through-put of animals in less time achieved. The automated system will lead to an increased understanding of the nature of bleeding following tail transection in different rodent models.
Keywords: Bleeding time; tail transection; animal model; instrumentation; rats